Socioeconomic differences in utilization of public and private dental care in Finland: Register-based evidence on a population aged 25 and over - Nurminen Mikko; Blomgren Jenni; Mikkola Hennamari (Public Library of Science, 2022)
Dental care utilization is known to have a strong socioeconomic gradient, with lower socioeconomic groups utilizing less of these services despite having poorer dental health. However, less is known about the utilization of dental services in the population concurrently in the public and private sectors in different socioeconomic groups. Additionally, evidence on how different sectors contribute to the overall socioeconomic gradient in dental care utilization is scarce. This study examines visits and absence of visits to public and private dentists in the years 2017–2018 by education, occupational class and income. Comprehensive register data was collected from the total population aged 25 and over in the city of Oulu, Finland (N = 118,397). The data were analyzed with descriptive methods and with multinomial logistic regressions for the probability of visits and with negative binomial regressions for the number of visits, adjusted for sociodemographic covariates. The results showed a clear socioeconomic gradient for the probability of visits according to income and education: the higher the income and the higher the education, the more likely was a visit to a dentist–especially a private dentist–during the two-year period. Similar results were obtained for the number of visits. Higher socioeconomic status was less associated with public dentist visits. While those with the lowest income visited public dentists more frequently than private dentists, their overall visits fell below that of others. Adjusted estimates by occupation did not show a clear socioeconomic gradient. The socioeconomic inequality in dentist visits in a country having a universally covered public dental care scheme puts a challenge for decision makers in designing an equal dental health care system. Experimenting with lower co-payments is a possible option.